Optimizing the Distribution Transformer Placement Based on the Maximum Loading and Drop Voltage at PLN Tegalsari Rayon - Fawzy Tio Prasetyo; Titiek Suheta (Procedia of Engineering and Life Science, 2021)
One of Problems in Indonesia regarding electricity distribution is far power station from the load (consumer). As a result, the electric energy distribution often becomes ineffective due to big enough voltage drop along the transmission and distribution channels. To overcome this problem, voltage drop must be reduced by placing the distribution transformer optimally. Therefore, this research aimed at determining the new distance from the transformer obtaining voltage drop above 10% along the channel of PLN Ltd in Tegalsari Rayon. For this reason, the researcher employed maximum loading on a certain bus or Continous Power Flow (CPF) and calculated the voltage drop in each channel simulated by Matlab. The simulation results demonstrated that bus 2 gained the maximum load 7.8 times, consequently, there were 15 buses getting voltage drop more than10%. Those buses comprised: bus 6 0.9%, bus 7 11.6%, bus 8 14.3%, bus 9 14.3%, bus 10 16.1%, bus 11 16.2%, bus 12 17.9%, bus 13 17.6%, bus 14 17.5%, bus 15 17%, bus 16 17%, bus 17 16.9%, bus 18 16.8%, bus 19 16.8%, and 20 16.8%. Meanwhile, the alteration of new distances occurring in several buses included: bus 6 from 151.9 m to 138.784 m, bus 7 from 48 m to 41.184 m, bus 8 from 211 m to 146.884 m, bus 9 from 50 m to 34.734 m, bus 10 from 205.89 m to 127.842 m, bus 11 to 167.01 m, bus 12 to 316.23 m, bus 13 to 141.44 m, bus 14 to 17.9 m, bus 15 to 1141.85 m, bus 16 to 19.61 m, bus 17 to 38.13 m, bus 18 to 59.31 m, bus 19 to 13.33 m, and 20 to 19.99 m.